Notary's Responsibility for Covernote Issuance as the Basis for the Bank's Trust in the Credit Agreement - Fa'idh Duhat; Ro'fah Setyowati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
Cover note as a certificate that the customer's land documents for credit applications are still in the process of certification, roya process, transfer of name, or splitting process if they are certified. However, in practice there are banks that use Covernote as a basis for credit disbursement. In matters of legal status, the Covernote issued by a Notary in the disbursement process carried out by the Bank and how the credit disbursement process by the Bank is based on the Covernote. This study aims to identify and explain the responsibilities of a Notary in publishing a Covernote and also the legal power of a Covernote. The discrepancy that occurs between the statement in the Covernote and the reality on the ground, the Notary must be responsible, whether criminally, civilly, or morally responsible.